Cross‐cultural adaption of the computerized assessment of information processing battery (COGNITO) for an Indian longitudinal study on rural elderly - Ammu Lukose; Rahul Kodihalli Venkatesh; Mino Susan Joseph; Palanimuthu T. Sivakumar; Girish N. Rao; Bangalore N. Gangadhar; Karen Ritchie; Aditi Balakrishnan; Vijayalakshmi Ravindranath; Naren P. Rao (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract Introduction Testing cognitive functions in Indians with low literacy and linguistic diversity is challenging. We describe the adaptation process of a comprehensive neurocognitive test battery to suit both literate and illiterate aging rural Indians. Methods Following the International Test Commission (ITC) guidelines for cross‐cultural adaptation, we adapted the COGNITO battery. This involved translating instructions, linguistic elements, and stimuli of each test from the original English version with the help of bilingual experts. Five stimuli across eight subtests were adapted to maintain construct equivalence and cultural relevance. Results The Kannada version of COGNITO, a digitally administered tool, was feasible and effective measure for assessing cognitive functions in Kannada‐speaking aging individuals from a rural Indian population. Discussion We emphasize the importance of maintaining semantic and theoretical construct equivalence with the source tool, and ensuring cultural and socioeconomic congruence for the cross‐cultural adaptation of computerized cognitive batteries. HIGHLIGHTS Assessed cognitive functions in rural elderly with low literacy and high linguistic diversity. Followed International Test Commission (ITC) guidelines for cross‐cultural adaptation to suit literate and illiterate aging rural Indians. Maintained semantic and theoretical construct equivalence with the source tool, ensuring cultural and socioeconomic congruence for cross‐cultural adaptation of cognitive batteries.